2014
DOI: 10.1186/1758-5996-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between circulating omentin-1 concentrations and components of the metabolic syndrome in adults without type 2 diabetes or cardiovascular disease

Abstract: BackgroundDysregulation of omentin-1, a beneficial adipokine, is thought to play a role in the development of type 2 diabetes and cardiovascular disease. The objective of this study was to evaluate the relationship between circulating omentin-1 concentrations and components of the metabolic syndrome in adults without type 2 diabetes or cardiovascular disease, and to determine if sex differences influenced the observed relationships.MethodsFasting blood samples were obtained from 93 adults, ages 30–60 years, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
4
29
1
1
Order By: Relevance
“…The second issue is the racial divergence in serum omentin concentration. Mean plasma omentin-1 concentrations were higher in African Americans than in Caucasians [40]. This aspect may lead to a discrepancy in the obtained results, because our study included only Caucasians, whereas the study by Nassif et al included Egyptian patients.…”
Section: Discussionmentioning
confidence: 63%
“…The second issue is the racial divergence in serum omentin concentration. Mean plasma omentin-1 concentrations were higher in African Americans than in Caucasians [40]. This aspect may lead to a discrepancy in the obtained results, because our study included only Caucasians, whereas the study by Nassif et al included Egyptian patients.…”
Section: Discussionmentioning
confidence: 63%
“…Our findings go beyond previous reports that were based on smaller samples and on univariate analyses. Most studies observed a positive association between omentin and HDL cholesterol (7,11,15,26,28,31), whereas the inverse association with triglycerides was found only in some (26,28), but not all (7, 11, 15, 16) samples.…”
Section: Omentin Lipid Levels and Adiponectinmentioning
confidence: 99%
“…Notably, the inverse relation between omentin levels on the one hand and 2-h glucose, 2-h insulin and ISI (composite), which represents an OGTT-derived measure of insulin sensitivity that is more closely related to clamp-measured insulin sensitivity than HOMA-IR (23), on the other hand remained significant after adjustment for BMI, but not after adjustment for lipids or adiponectin. Some (10,26), but not other (7,11,27,28), studies reported inverse associations between omentin and fasting glucose in univariate analyses. One study reported inverse associations with fasting glucose, 2-h glucose and HbA1c in univariate, but not in multivariate analyses (12).…”
Section: Omentin and Glucose Metabolismmentioning
confidence: 99%
“…It was also reported that blood omentin concentration decreased in the obese diabetic woman (119 ng/ml) compared with that in the nondiabetic obese woman (207 ng/ml) (17). In addition, it was reported that blood omentin concentration decreased in the men with metabolic syndrome (130 ng/ml) compared with the men without metabolic syndrome (186 ng/ml) (19). From these reports, it is considerable that the concentration of omentin used in this study is within the (patho)physiological range.…”
Section: Discussionmentioning
confidence: 89%
“…Secretion and plasma concentration of omentin decrease in the obese subjects (1). A decrease in circulating omentin level is related to the occurrence of type 2 diabetes and metabolic syndrome (19). It was also demonstrated that a decrease in circulating omentin level independently correlated with an increased arterial stiffness and carotid plaque in type 2 diabetes (24).…”
mentioning
confidence: 80%